2015
DOI: 10.1186/s12906-015-0847-5
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and in vitro anticancer activities of phenolics isolated from sugar beet molasses

Abstract: BackgroundIn the present study, the phenolic compounds were prepared using ultrasonic-aid extraction from sugar beet molasses (SBM).MethodsGallic acid (GA), cyanidin-3-O-glucoside chloride (CGC) and epicatechin (EP) were produced after column chromatography from the extraction, and further detected using NMR, QTOF-MS and ESI-MS/MS.ResultsThe three compounds exhibited strong antioxidant activities including DPPH radical scavenging activities, ABTS radical scavenging activities and ORAC values. GA showed the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 31 publications
0
35
0
1
Order By: Relevance
“…This concentration of Que was not deemed cytotoxic in our IPEC-J2 cells. Furthermore, anti-proliferative activities of GA were observed in Caco-2, HepG2, MCF-7, and WT-F344 rat liver cells using the 3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide (MTT) assay and were suggested to be caused by the pro-oxidative effects of GA [30]. Thus, GA shows selective cytotoxicity for cancerous human cells, but, in our setting, very little toxicity for normal porcine cells.…”
Section: Discussionmentioning
confidence: 99%
“…This concentration of Que was not deemed cytotoxic in our IPEC-J2 cells. Furthermore, anti-proliferative activities of GA were observed in Caco-2, HepG2, MCF-7, and WT-F344 rat liver cells using the 3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide (MTT) assay and were suggested to be caused by the pro-oxidative effects of GA [30]. Thus, GA shows selective cytotoxicity for cancerous human cells, but, in our setting, very little toxicity for normal porcine cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, structure activity relationship studies delineating the key functional groups required for exhibiting potent anti-cancer effects of phenolic compounds have identified the involvement of aromatic ring and hydroxylic groups [40, 41], (Fig. 4).…”
Section: Key Structural Features and Mechanism Of Action Of Plant Phementioning
confidence: 99%
“…In addition to hydroxylic groups and catechol ring structure, the presence of an unsaturated short fatty acid side chain also makes the phenolic compounds more potent. As an example, studies comparing the efficacy of cinnamic acid and benzoic acid for inhibiting cancer cell growth revealed that cinnamic acids that contain a unsaturated propionic acid side chain are more better anti-cancer agents [40, 41]. Thus phenolic acids i.e benzoic and cinnamic acid derivatives with higher hydroxyl substitutions could be considered as potential candidates for preventing the cancer cell proliferation.
Fig.
…”
Section: Key Structural Features and Mechanism Of Action Of Plant Phementioning
confidence: 99%
“…These phytochemicals possess many biological activities and a documented positive impact on human health. There are data about the antioxidant, anti‐allergic, anti‐atherosclerotic, anti‐inflammatory, antibacterial and antithrombotic properties of phenolic compounds (Del Rio et al ., ; Chen et al ., ; Díaz‐de‐Cerio et al ., ; Marhuenda et al ., ). Most of these studies were conducted as in vitro experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Many biological activities of phenolic compounds, especially antioxidant, immunological, anti‐inflammatory, antiproliferative and hypoglycaemic effects, are well documented (Chen et al ., ; Díaz‐de‐Cerio et al ., ; Marhuenda et al ., ). The stability of phenolic compounds as well as the binding or release thereof from various combinations due to in vitro digestion may influence the biological activity of these compounds measured after digestion.…”
Section: Introductionmentioning
confidence: 99%